2008
DOI: 10.1038/sj.bjc.6604514
|View full text |Cite
|
Sign up to set email alerts
|

A role for topoisomerase IIα in the formation of radiation-induced chromatid breaks

Abstract: Chromatid breaks in cells exposed to low dose irradiation are thought to be initiated by DNA double-strand breaks (DSB), and the frequency of chromatid breaks has been shown to increase in DSB rejoining deficient cells. However, the underlying causes of the wide variation in frequencies of G2 chromatid breaks (or chromatid 'radiosensitivity') in irradiated T-lymphocytes from different normal individuals and cancer cases are as yet unclear. Here we report evidence that topoisomerase IIa expression level is a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…[32][33][34][35] A previous study showed that TOPO2A contributes to forming chromatid breaks in radiation-exposed cells. 27 Here, we report that TOPO2A protein levels were increased by 5-Aza treatment of RR-Hep-2 cells (Fig. 6C and E), and that the promoter demethylation of TOPO2A was closely mirrored by an increase of its decatenation activity in Hep-2 and RR-Hep-2 cells (Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[32][33][34][35] A previous study showed that TOPO2A contributes to forming chromatid breaks in radiation-exposed cells. 27 Here, we report that TOPO2A protein levels were increased by 5-Aza treatment of RR-Hep-2 cells (Fig. 6C and E), and that the promoter demethylation of TOPO2A was closely mirrored by an increase of its decatenation activity in Hep-2 and RR-Hep-2 cells (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…27 To examine the cellular effects of 5-Aza (5 mM)-induced TOPO2A expression in Hep-2 and RR-Hep-2 cells, we conducted clonogenic survival assays. Our results revealed that 5-Aza treatment significantly reduced the survival of Hep-2 and RRHep2 cells exposed to various doses of radiation (Fig.…”
Section: Demethylation Of Hep-2 and Rr-hep-2 Cells Increases Transcrimentioning
confidence: 99%
“…The chromatid break frequency and topoisomerase IIa expression (ELISA assay) are being compared in 3-day-stimulated peripheral blood T lymphocytes from a group of breast cancer patients and control individuals exposed to a low dose of γ-radiation. Results We show that chromatid radiosensitivity (based on the frequency of metaphase chromatid breaks in irradiated G 2 cells) is significantly lower in a topoisomerase IIa underexpressing variant cell lines [5], and preliminary results show that reducing expression with SiRNA also reduces chromatid radiosensitivity. In a pilot study we are currently comparing the chromatid radiosensitivity and topoisomerase IIa expression in stimulated peripheral blood lymphocytes of a group of Tayside breast cancer patients and a similar number of normal noncancer control individuals.…”
mentioning
confidence: 70%
“…There are very few studies investigating DNA repair and DSBs in HL60 cells (14). Res-HL60 cells established in our study were different from the cells from which they originated in terms of size, and DNA repair and proliferation activities.…”
Section: Discussionmentioning
confidence: 99%